Implementasi Intervensi Komunitas: Sosialisasi Kepemimpinan untuk Regenerasi Pengurus Karang Taruna di Desa Wringinanom: - - Adista, Ayu Aulia; Permatasari, Vira; Azzahiya, Hilya; Bening, Dinda; Farida, Nafilatul (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Wringinanom Village, strategically located as a buffer zone for Bromo Tengger Semeru National Park (TNBTS), holds significant potential in agriculture and tourism. However, since 2019, the village’s youth organization, Karang Taruna, has faced inactivity due to a lack of leadership regeneration and the impact of the COVID-19 pandemic, which disrupted the social activities of the village youth. Through a community service program, community-based interventions were implemented using community mapping and focus group discussion (FGD) methods to reactivate Karang Taruna. The program's outcomes include the establishment of a functional new organizational structure, increased youth participation, and empowerment through leadership training. Additionally, the program strengthened collaboration between youth, community leaders, and the village government to support sustainable village development. Recommendations for follow-up actions include developing entrepreneurial and social programs, as well as conducting regular monitoring and evaluation to ensure organizational sustainability.